Embryology and adult urology – Not always mutually exclusive: A case report on true hermaphroditism at an adult urology clinic - Turo, Rafal; Derbyshire, Laura F; Smolski, Michal; Collins, Gerald N; Lynch, Niall; Lewinski, Maryna; Brough, Richard J; Sinclair, Andrew M (Canadian Urological Association Journal, 2014)
True hermaphrodite (TH) is one of the rarest varieties of disorders of sexual differentiation. Most patients present early in the life and are managed by pediatricians. We present a rare case of an adult TH which was first diagnosed by a urologist. We discuss the pathology of TH and its clinical relevance. Knowledge and awareness of embryology are vital to all specialties.